2016
DOI: 10.21037/jtd.2016.09.10
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of lung cancer and urban spatial factor: based on survey in Shanghai

Abstract: Background: The density of particulate matter (PM) in mega-cities in China such as Beijing and Shanghai has exceeded basic standards for health in recent years. Human exposure to PMs has been identified as traceable and controllable factor among all complicated risk factors for lung cancer. While the improvement of air quality needs tremendous efforts and time, certain revision of PM's density might happen associated with the adjustment of built environment. It is also proved that urban built environment is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Epidemiological studies of lung cancer have identified risk factors for lung cancer such as smoking, passive smoking, familial inheritance, air pollution (outdoor and indoor air pollution), work environment exposure and diet [38]. Relevant studies have identified certain factors of urban built environment affecting outdoor air pollution, including land use, spatial form, transportation system, green space and public open space [39]. The scale and layout of specific types of land use may affect outdoor air pollution, thus affecting respiratory health, including industrial land [40,41,42,43,44], cultivated land [44], residential land [40,41,42,44] and waterbody [42,44].…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies of lung cancer have identified risk factors for lung cancer such as smoking, passive smoking, familial inheritance, air pollution (outdoor and indoor air pollution), work environment exposure and diet [38]. Relevant studies have identified certain factors of urban built environment affecting outdoor air pollution, including land use, spatial form, transportation system, green space and public open space [39]. The scale and layout of specific types of land use may affect outdoor air pollution, thus affecting respiratory health, including industrial land [40,41,42,43,44], cultivated land [44], residential land [40,41,42,44] and waterbody [42,44].…”
Section: Methodsmentioning
confidence: 99%
“…In the cross-sectional studies, several positive outcomes and a few neutral findings were reported. Positive outcomes included: lower prevalence of lung cancer associated with green space covered with trees within residential areas [49]; lower prevalence of asthma among children associated with greater street tree density [50]; and reduced asthma hospitalization associated with tree density during periods with high ambient pollutant concentrations [51]. Neutral findings included: no significant association between street tree density and asthma hospitalization among children [50]; and no significant association between tree density and asthma hospitalization during periods with lower ambient pollutant concentrations [51].…”
Section: Air Pollutants and Respiratory Conditionmentioning
confidence: 99%
“…Various previous studies indicated that neighborhood greenspace affects building occupant health. Researchers tend to associate this result with the opportunity provided to occupants to walk and exercise (e.g., [44,66]. In current study, even though half of the buildings are located in areas surrounded by large greenspace, majority of these green areas are not accessible (fall outside the premises area) (refer to Fig.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, the roles of greenspace have found to be especially significant in protecting building occupants from health hazards related to air pollution and extreme temperature (e.g. [11], and in promoting healthy behaviors amongst building occupants, such as physical activities (e.g., [44,66].…”
Section: Neighborhood Environment and Building Occupantsmentioning
confidence: 99%